Duckweed application in nature-based system for water phytoremediation and high-value coproducts at family agrisystem from a circular economy perspective - Heitzman, Beatriz S. [UNESP]; Bueno, Guilherme W. [UNESP]; Camargo, Tavani R. [UNESP]; Proença, Danilo C. [UNESP]; Yaekashi, Carlos T.O. [UNESP]; da Silva, Regildo M.G. [UNESP]; Machado, Levi P. [UNESP] (Elsevier, 2024)
Duckweeds are widely recognized for their efficiency in the phytoremediation of agricultural and industrial effluents. This study had two main objectives: 1) Implement a Nature-based Solutions (NBS) utilizing the environmental services of duckweeds to improve water quality through phytoremediation in small fish farms; 2) Analysis of duckweeds biomass produced in these fish farms to develop coproducts from a circular economy perspective in family agrisystem in Brazilian Atlantic Forest. The effectiveness of the phytoremediation system was assessed by the reduction of the Trophic State Index (TSI). Phytoremediation in small fish farming NBS was implemented using Clarias gariepinus, employing two different managements approaches: (i) System I – L. minor cultured every 15 days, with biomass harvest and effluent analysis conducted in each cycle over 60 days; (ii) System II – L. minor cultured every 30 days, following a similar cycle and analysis. Additionally, effluent from fish production underwent testing for phytoremediation in a batch system within a climate-controlled laboratory. L. minor demonstrated efficiency in System II, leading to a reduction of the TSI. The dry biomass of the plants emerged as a viable source of amino acid for application in functional foods and feed or nutraceuticals. The findings underscore the potential integration of L. minor into the NBS system and the generation of new co-products from circular production. In addition to its effective phyto- remediation properties, L. minor's dry biomass exhibited appealing characteristics, with elevated levels of crude protein, minerals, fatty acids, and carotenoids. This positions L. minor as a promising candidate for developing bioproducts tailored for functional foods and nutraceuticals. This underscores the potential of duckweeds to produce valuable nutritional compounds beyond their remediation capabilities.
Keywords: Bioproducts; Lemna minor; Phytoremediation; Plant protein; Trophic State Index